Integration Innovation of Big Data Analysis and Artificial Intelligence in the Field of Education - Xiu, Le (International Journal of Social Sciences and Public Administration, 2024)
The education industry is undergoing a major transformation driven by big data and artificial intelligence technology (AI). With the help of big data analysis, education can rely on big data processing and deep mining to provide a solid data foundation for the construction of customized learning paths. AI technology enhances the intelligence and personalization of teaching through intelligent tutoring systems and virtual learning platforms. As students of all ages advance in their education, the evolving field of information science remains adaptable, enriching learning experiences across diverse needs. The popularization of technology has also triggered a series of issues such as data protection and equal educational opportunities. This article analyzes the theoretical foundation of big data and AI, explores the core application scenarios and current situation in the field of education, and proposes integrated and innovative solutions to provide a new perspective for educational technology innovation.